Lipid nanoparticles employed in mRNA-based COVID-19 vaccines: an overview of materials and processes used for development and production - Pantelić, Ivana; Ilić, Tanja; Nikolić, Ines; Savić, Snežana (Archives of Pharmacy, 2022)
In the light of the recommended application of the third dose, both public and professional community would benefit from a detailed report on the technological advances behind the developed messenger ribonucleic acid (mRNA) based COVID-19 vaccines. Although many vaccine developers are yet to reveal their precise formulations, it is apparent they are founded on nanotechnology platforms similar to the one successfully used for registered drug OnpattroTM (INN: patisiran). Optimal encapsulation of mRNA requires the presence of four lipids: an ionizable cationic lipid, a polyethylene-glycol (PEG)-lipid, a neutral phospholipid and cholesterol. Together with other excipients (mainly buffers, osmolytes and cryoprotectives), they enable the formation of lipid nanoparticles (LNPs) using rapid-mixing microfluidic or T-junction systems. However, some limitations of thermostability testing protocols, coupled with the companies’ more or less cautious approach to predicting vaccine stability, led to rigorous storage conditions: -15° to -25°C or even -60° to -80°C. Nevertheless, some inventors recently announced their mRNA-LNP based vaccine candidates to be stable at both 25° and 37°C for a week. Within the formulation design space, further optimization of the ionizable lipids should be expected, especially in the direction of increasing their branching and optimizing pKa values, ultimately leading to the second generation of mRNA-LNP COVID-19 vaccines.
Keywords: lipid nanoparticles; ionizable lipid; PEG-lipid; microfluidic device; storage conditions